Beta‐blockers may reduce intrusive thoughts in newly diagnosed cancer patients. Issue 8 (17th December 2012) - Lindgren, Monica E.; Fagundes, Christopher P.; Alfano, Catherine M.; Povoski, Stephen P.; Agnese, Doreen M.; Arnold, Mark W.; Farrar, William B.; Yee, Lisa D.; Carson, William E.; Schmidt, Carl R.; Kiecolt‐Glaser, Janice K.
Abstract: Objective: A cancer diagnosis provokes significant levels of emotional distress, with intrusive thoughts being the most common manifestation among breast cancer survivors. Cancer‐related intrusive thoughts can take the form of emotional memories, flashbacks, nightmares, and intrusive images. Emotional arousal after a severe life stressor prolongs adrenergic activation, which in turn may increase risk for post‐traumatic symptomatology. However, antihypertensive beta‐blockers block adrenergic activation and are known to reduce traumatic memories and related psychological distress. Thus, the current study examined the association between beta‐blocker use and the severity of cancer‐related intrusive thoughts and related symptoms following a cancer diagnosis. Methods: The 174 breast and 36 female colorectal cancer patients who had recently undergone diagnostic screening or biopsy included 39 beta‐blocker users and 171 non‐users. Prior to any cancer treatment including surgery, participants completed questionnaires that included the Impact of Events Scale and the Center for Epidemiological Studies Depression Scale. Analyses controlled for age, education, cancer stage, cancer type, days since diagnosis, marital status, depression, and comorbidities. Results: Although the high rates of cancer‐related distress in this sample were similar to those of other studies with recently diagnosed patients, beta‐blocker users endorsed 32% fewer cancer‐related intrusive thoughts than non‐users. Conclusions: Recently diagnosed cancer patients using beta‐blockers reported less cancer‐related psychological distress. These results suggest that beta‐blocker use may benefit cancer patients' psychological adjustment following diagnosis, and provide a promising direction for future investigations on the pharmacological benefits of beta‐blockers for cancer‐related distress. Copyright © 2012 John Wiley & Sons, Ltd.